TEACHER-STUDENT VERBAL INTERACTION PATTERN IN READING CLASSROOM SMP PARULIAN 2 MEDAN - Nurcahaya Sinaga; Siti Aisah Ginting; Farida Hanim Saragih (Universitas Negeri Medan, 2021)
TEACHER-STUDENT VERBAL INTERACTION PATTERN INREADING CLASSROOM SMP PARULIAN 2 MEDAN*Nurcahaya Sinaga** Dr. Siti Aisah Ginting M.Pd.** Farida Hanim Saragih, S.Pd., M.HumABSTRACTNurcahaya Sinaga. Registration Number: 2153321022. Teacher-StudentVerbal Interaction Pattern in Reading Classroom at SMP Parulian 2 Medan.A Thesis. English and Literature Department. Faculty of Languages andArts. State University of Medan, 2020.This research was intended to examine the verbal interaction features used by twoteachers in teaching reading comprehension through virtual classroom with zoomapplication. This virtual class was chosen since the offline classroom was changedinto online classroom during the covid 19 pandemic. This research was conductedto answer the research problems; 1. How are the teachers and the students verbalinteraction patterns used in reading classroom of SMP Parulian 2 Medan. 2 Whydo the teachers interact in the way they do? It covers the analysis on thetranscripts of teachers-student verbal interaction and the interview. The analysiscovers the steps of data condensation. In the process of data condensing, allrecorded utterances were selected to focus on the utterances used by the teachersand students during the virtual classroom. Then, the utterances were simplified inorder to be easier to understand. The abstracting process was done to focus on theintention of answering the research problems. The final step was transforming theutterances and interview into transcription. The design of this research is a casequalitative study. The subjects were two English teachers and twenty students ofParulian Junior High School. The data to answer the problems were transcripts ofverbal interaction used by the teachers and students and interview to find thereasons of the teachers to use certain patterns students during the virtualclassroom. The data were collected by using recording tools; smart phonerecording and observational notes. The findings show that the teachers’ verbalclassroom interaction did not cover all types of interactional features by Walsh.The verbal interactions through zoom virtual classroom by the first teacher consistof seven types of interactional features. They are Display questions (0,53%),Seeking clarification (0,21%), Extended wait-time (0,125%), Scaffolding(0,003%), Direct repair (0,003%), Confirmation checks (0,003%), Teacher echo(0,003%). While. The verbal interactions through zoom virtual classroom by thesecond teacher consist of seven types of interactional features. They are Display questions (0,29%), Scaffolding (0,023%), Extended wait-time (0,23%), Seekingclarification(0,12%), Confirmation checks (0,032%), Teacher interruptions(0,032%), Direct repair (0,016%), Content feedback ( 0,016%), Extended learnerturn (0,016%), Teacher echo (0,016 %). The most frequently used of interactionalfeature is display questions. The reason to use display questions is material focus.The teachers wanted the students to focus on the material.Keywords: Classroom Verbal Interaction, Pedagogical goal, ReadingClassroom.